2005
DOI: 10.1098/rspb.2004.2942
|View full text |Cite
|
Sign up to set email alerts
|

Character complexity and redundancy in writing systems over human history

Abstract: A writing system is a visual notation system wherein a repertoire of marks, or strokes, is used to build a repertoire of characters. Are there any commonalities across writing systems concerning the rules governing how strokes combine into characters; commonalities that might help us identify selection pressures on the development of written language? In an effort to answer this question we examined how strokes combine to make characters in more than 100 writing systems over human history, ranging from about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 15 publications
2
77
1
Order By: Relevance
“…Many of our other human inventions have been designed-either explicitly or via cultural selection over time-so as to minimize their demands on the brain. For example, writing and other human visual signs appear to have been optimized by cultural selection for our visual systems (Changizi, 2006(Changizi, , 2009Changizi & Shimojo, 2005;Changizi, Zhang, Ye, & Shimojo, 2006). The definitions in the dictionary are not identical to the meanings of words we have in our heads, missing out, for example, on metaphorical associations that may be part of an individual's meaning of the word (see, e.g., Fillmore, 1975;Lakoff & Johnson, 1980, 2003, but it would be surprising if the large-scale organization of the dictionary was not driven in some large part by the organization of our mental lexicon.…”
Section: Resultsmentioning
confidence: 99%
“…Many of our other human inventions have been designed-either explicitly or via cultural selection over time-so as to minimize their demands on the brain. For example, writing and other human visual signs appear to have been optimized by cultural selection for our visual systems (Changizi, 2006(Changizi, , 2009Changizi & Shimojo, 2005;Changizi, Zhang, Ye, & Shimojo, 2006). The definitions in the dictionary are not identical to the meanings of words we have in our heads, missing out, for example, on metaphorical associations that may be part of an individual's meaning of the word (see, e.g., Fillmore, 1975;Lakoff & Johnson, 1980, 2003, but it would be surprising if the large-scale organization of the dictionary was not driven in some large part by the organization of our mental lexicon.…”
Section: Resultsmentioning
confidence: 99%
“…A cross-linguistic study comparing more than 100 alphabetic and nonalphabetic scripts showed that writing systems share a similar number of strokes per symbol, with three strokes per character on average (e.g., Changizi & Shimojo, 2005). Moreover, there is high redundancy within sets (around 50%) reflecting the tendency to re-use the same types of strokes rather than to create new ones.…”
Section: Why and How Devising A Set Of Artificial Characters?mentioning
confidence: 99%
“…This could be sufficient for certain nonlinguistic studies, but it is definitely not valid when the aim is to closely reproduce situations of exposure to natural print. In real writing systems, the number of characters varies from 6 to 180, but only two writing systems (out of more than 100) have less than ten characters, and the average number is 32 (Changizi & Shimojo, 2005). In both sets, we therefore created a number of characters similar to the number of letters in the Latin alphabet (i.e., 24 for BACS-1 and 26 for BACS-2).…”
Section: Why and How Devising A Set Of Artificial Characters?mentioning
confidence: 99%
See 1 more Smart Citation
“…Changizi et al supported their thesis by finding commonalities in contour configurations across writing systems, nonlinguistic symbols, and natural scenes. In a further study of letter components, Changizi and Shimojo (2005) concluded that writing systems have evolved to balance distinctiveness and uniformity. Parallels between object perception and letter design were also studied by Lanthier, Risko, Stolz and Besner (2009).…”
Section: Font Typicality Type Design and Languagementioning
confidence: 99%